A smartphone-based point-of-care quantitative urinalysis device for chronic kidney disease patients. (1st August 2018) - Akraa, Shaymaa; Pham Tran Tam, Anh; Shen, Haifeng; Tang, Youhong; Tang, Ben Zhong; Li, Jimmy; Walker, Sandy
Abstract: This paper presents the design and development of a smartphone-based urinalysis device that has the ability for chronic kidney disease (CKD) patients themselves to conduct rapid and reliable quantitative urinalysis of human serum albumin (HSA) using an aggregation-induced emission (AIE) nanomaterial bioprobe with their own smartphones. The focus of this paper is a novel solution to the device agnosticism issue as a wide diversity of smartphones co-exist in the market. The solution comprises: a) custom-design and fabrication of an imaging housing that provides a consistent imaging condition regardless of the physical dimensions and the camera position of the smartphone used, b) orchestration of an image processing and analysis process that produces consistent image colour intensity values regardless of the camera sensor and imaging software used by the smartphone, and c) special design and development of an intuitive cross-platform mobile application that is scalable to growth, adaptable to changes, resilient to loss of data, and has an extremely low requirement for smartphone hardware. Preliminary evaluation of the device has confirmed the effectiveness of the proposed solution and the viability of such a smartphone-based device for people who have already developed or are prone to CKD to regularly perform point-of-care (POC) urine testing in order to self monitor their own health conditions without the burden of frequent visits to their doctors. Highlights: uTester allows chronic kidney disease patients themselves to conduct urine tests with their own smartphones anywhere. uTester provides rapid and reliable full-quantitive urinalysis results. uTester is device-agnostic and supports a wide range of smartphones. uTester is cloud-based and has an extremely low requirement for smartphone hardware. uTester integrates remote diagnosis and telemedicine.